Edukasi Bidang Kesehatan Melalui Budidaya Dan Olah Desain Lahan Tanaman Obat Untuk Masyarakat Desa Ngronggot Kabupaten Nganjuk - Jawa Timur (Fakultas Teknik, Universitas Brawijaya, 2025)
Health facilities in Nganjuk Regency, East Java, especially in Ngronggot Village, remain limited. These facilities serve multiple villages and are located far from residential areas, making access challenging for the residents of Ngronggot Village. Consequently, villagers often resort to herbal remedies for treating and preventing illnesses instead of visiting health centers or using chemical-based drugs. Recognizing this issue, a private entrepreneur who owns a farm in the area donated a 500-square-meter plot of land to establish a simple clinic integrated with a medicinal plant garden. To implement this initiative, a collaboration was formed involving architecture lecturers from FTUB, tasked with designing the clinic and garden; chemical engineering lecturers from FTUB, experienced in environmental science and TOGA garden development; and pharmacy students from FKUB alongside young doctors from Airlangga University. These professionals and students will educate the community and local health teams on the benefits and uses of medicinal plants. Additionally, the HERBAKU application will be developed as an integrated Health Information System to streamline access to health services for both healthcare workers and villagers. This collaborative effort bridges academia and industry, with support from the entrepreneur who donated the land, academics from Brawijaya University, and DUDI (farm entrepeneur). Together, they aim to improve public health in Ngronggot Village by enhancing healthcare accessibility and empowering the community with knowledge about medicinal plants and integrated health services. This initiative represents a significant step towards addressing healthcare disparities in rural East Java.